CORPORATE SUSTAINABILITY PERFORMANCE AND FINANCIAL PERFORMANCE: MODERATING EFFECT OF BOARD COMPOSITION - Nurlaily, Ferina; Rahmi, Ahadiyah Adinia (Faculty of Economics and Business University of Mataram, 2021)
This study analyzes the moderating effect of the composition of female directors and the composition of independent directors on CSP and ROA. The purpose of this study is to analyze the effect of the disclosure of Corporate Sustainability Performance (CSP) on the Return on Assets (ROA) as a proxy for the company's financial performance. The population of this study is companies listed on the SRI-KEHATI index during the period November 2016– October 2019. The research hypotheses were tested using linear regression analysis and moderated regression analysis. The study results found that CSP has a significant effect on the company's ROA. The better and more complete the CSP disclosure, the higher the ROA. Furthermore, the composition of female and independent directors does not significantly affect CSP on corporate financial performance. This study implies that female directors and the composition of the independent board are more for compliance with regulatory requirements.